Paul's world - Porter, Stanley E., 1956- (Pauline studies ;, 2008)
This volume is concerned with Paul's world. The major question to ask is - what is that world of Paul? In determinable ways, Paul's world is everything in the world in which Paul lived and acted, and hence virtually everything that Paul did. In other words, Paul's world can be defined macrocosmically and microcosmically. As the term is defined in the various essays in this volume, Paul's world includes the surrounding environment in which Paul functioned, including its various religious, social, cultural, literary, rhetorical, linguistic and related phenomena. This volume treats some of the mo.